Rheumatic heart disease and endomyocardial fibrosis: Distinguishing the etiology of mitral regurgitation in low-resourced areas - Mocumbi, Ana Olga; Madeira, Geoffrey; Beaton, Andrea (SA Heart Journal, 2017)
Rheumatic heart disease (RHD) and endomyocardial fibrosis (EMF) are 2 neglected cardiovascular diseases that disproportionately affect young populations, living in poverty. RHD characteristically occurs in low- and middle-income countries, as well as in some disadvantaged populations within high-income countries, such as the Aboriginal peoples of Australia. In contrast, EMF is primarily a tropical cardiomyopathy, with both high-prevalence countries and high-prevalence regions within affected countries. The etiology, pathogenesis, echocardiographic findings, interventions and prognosis are quite distinct. While RHD is unarguably the most preventable of all cardiac diseases, resulting from untreated or undertreated group A streptococcal infections, EMF’s etiology remains unclear. It has been related to infections, dietary factors and toxic agents, and currently there are no specific drugs to treat EMF. The distinction of mitral lesions due to RHD from leftsided EMF, can be difficult in endemic areas for both diseases, especially in the context of lack of resources for diagnosis. However, the correct distinction is highly important since medical management, surgical and interventional options and prognosis are considerably different. Here we describe the features that allow this distinction in African settings where both diseases occur, paying particular emphasis to echocardiography.